Cement-based grouting materials for semi-flexible pavement

By combining modified polycarboxylate superplasticizer with sulfoaluminate cement, the problem of slow early strength of traditional superplasticizers has been solved, achieving early strength and uniformity of cement-based grouting materials for semi-flexible pavements, which is superior to commercially available products.

CN119080463BActive Publication Date: 2025-01-10XIAN BEIJIAO MUNICIPAL FACILITIES MAINTENANCE MANAGEMENT CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411576776.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-10
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Traditional polycarboxylate superplasticizers result in slow early strength growth in concrete and unstable compounding effects, making it difficult to meet the needs of different application environments.

Method used

A modified polycarboxylate superplasticizer is prepared by combining a modified polycarboxylate superplasticizer with sulfoaluminate cement, fly ash, quartz sand, coal-fired power plant slag, defoamer, and UEA expansion agent to form a cement-based grouting material for semi-flexible pavement.

Benefits of technology

It achieves early strength growth and uniform and stable slurry, with significant water reduction effect, meets national standards, and requires no additional additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The present application provides a cement-based grouting material for semi-flexible pavement, which belongs to the field of concrete, and specifically relates to a modified polycarboxylate water-reducing agent and a preparation method of the modified polycarboxylate water-reducing agent, and contains a cement-based grouting material for semi-flexible pavement with a modified polycarboxylate water-reducing agent. The material contains the following components in percentage by weight relative to sulphoaluminate cement: sulphoaluminate cement, 10-15% grade II fly ash, 15-25% 40-200 mesh quartz sand, 15-25% fineness 1.6-3 coal-fired power plant slag, 0.5-1% modified polycarboxylate water-reducing agent, 0.01-0.2% defoaming agent, 4-10% UEA expansion agent, and a modified polycarboxylate water-reducing agent prepared according to the method of the present invention. The material has many advantages such as overcoming the problem of slow setting of traditional polycarboxylate water-reducing agents, early strength, uniform and stable slurry, and no need for additional additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of concrete, and specifically relates to a modified polycarboxylate water reducer, a preparation method of the modified polycarboxylate water reducer, and a cement-based grouting material for a semi-flexible pavement containing the modified polycarboxylate water reducer. Background Art

[0002] Common pavements include asphalt concrete pavement and cement concrete pavement. Cement concrete pavement is basically a rigid pavement with relatively poor driving comfort. Asphalt concrete pavement is a common pavement structure. Currently, 80% of high-grade highways are asphalt pavement structures, which have the advantages of strong traffic comfort, low traffic noise and fast traffic opening. However, asphalt materials are viscoelastic and highly sensitive to temperature. In summer, when the temperature is high, the viscosity of asphalt materials decreases, and the cohesion between aggregate particles weakens. After a long period of vehicle rolling, the asphalt mixture on the road surface produces inter-particle slip, which eventually leads to shear deformation damage such as rutting, potholes, and waves in the asphalt pavement structure layer, reducing the comfort and safety of drivers; in winter, when the temperature is low, the mechanical properties of asphalt concrete road structure materials are improved to a certain extent, but also due to the increase in the viscosity of asphalt materials, the road surface deformation resistance is greatly reduced, and the overall performance is brittle, which eventually leads to cracking of the pavement structure layer.

[0003] As a new type of pavement structure that combines rigidity and flexibility, semi-flexible pavement has the advantages of both rigid and flexible pavements. Cement-based grouting materials for semi-flexible pavements are special engineering materials that use special cement as the main cementitious material, with fine aggregate, mineral admixtures and a variety of high-performance admixtures added. They have an important influence on the road performance of semi-flexible pavements. However, the application of semi-flexible pavements in my country is still in its early stages. Technologies in all aspects need to be further improved. Water reducers are an important part of the synthesis of semi-flexible pavements. Compared with small molecule water reducers, polycarboxylic acid polymer water reducers have a huge space for molecular structure regulation, providing a variety of ways to optimize their performance, such as increasing the water reduction rate, developing early and late strength of concrete, and even controlling the autogenous shrinkage and drying shrinkage of concrete.

[0004] At present, the most widely used water reducer in the market is polycarboxylate water reducer, which has the advantages of low dosage, high water reduction rate, low shrinkage, safety and environmental protection, and strong molecular structure design ability. However, traditional polycarboxylate water reducer has a strong delay effect on cement hydration in concrete system, resulting in slow growth of early strength of concrete. In order to solve this problem, the usual solution is to use traditional early strength agent in combination with polycarboxylate water reducer. However, the effect of compounding is unstable, and different formulas are required for different use environments.

[0005] Therefore, a water reducing agent that overcomes the defects of the prior art is developed and applied to cement-based grouting materials for semi-flexible pavements. Summary of the invention

[0006] In order to overcome the defects of the prior art, the present invention provides a cement-based grouting material for semi-flexible pavement containing a designed modified polycarboxylate water reducer:

[0007] Contains the following components in percentage by weight relative to sulphoaluminate cement: sulphoaluminate cement, 10-15% Grade II fly ash, 15-25% 40-200 mesh quartz sand, 15-25% 1.6-3 fineness coal power plant slag, 0.5-1% modified polycarboxylate water reducer, 0.01-0.2% defoamer, 4-10% UEA expansion agent;

[0008] In addition, the present invention also provides a method for preparing the modified polycarboxylic acid water-reducing agent;

[0009] The preparation method of the modified polycarboxylate water-reducing agent is:

[0010] (1) Polyethylene glycol acrylate is prepared by reacting acrylic anhydride with PEG-200;

[0011] (2) N,N-dimethylacrylamide reacts with butane sultone to prepare 4-(N,N-dimethyl-N-acryloyl)aminobutane sulfonic acid salt, the structure of which is ;

[0012] (3) Alkenyl carboxylic acids having the following structure: , where n = an integer from 1 to 3;

[0013] (4) Deionized water is added to the reaction kettle, and then the monomers prepared in steps (1), (2) and (3) are added in a molar ratio of acrylate polyethylene glycol ester: 4-(N,N-dimethyl-N-acryloyl)aminobutanesulfonic acid inner salt: alkenyl carboxylic acid of 1:0.5-2:0.5-2, and an initiator ammonium persulfate and a chain transfer agent mercaptopropionic acid are added. The mixture is stirred at 40-60° C. for 6-10 hours, and then sodium hydroxide is added to adjust the pH to 6-7.

[0014] The amount of other components is calculated based on the sulphoaluminate cement, that is, based on the mass of the sulphoaluminate cement, other components are added according to the above percentages. The sulphoaluminate cement can be a conventional product that meets national standards.

[0015] The amount of water added when using this product can be adjusted according to actual needs, preferably 50% of the cement weight.

[0016] Among them, the Class II fly ash is a commercial product that meets the requirements of the national standard GB / T1596-2017 "Fly Ash". Its relative dosage to sulphoaluminate cement is 10-15%.

[0017] The quartz sand is selected to have a mesh size of 40-200, i.e., 50, 60, 70, 80, 90, 100, 150, 200, preferably 100, 150, 200, more preferably 200. The relative amount of quartz sand to sulphoaluminate cement is 15-25%.

[0018] Among them, the slag from coal-fired power plants selects slag with a fineness of 1.6-3, which can be slag with a fineness of 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.5, 2.8, and 3.0.

[0019] The defoaming agent is polydimethylsiloxane, and its dosage relative to sulphoaluminate cement is 0.01-0.2%.

[0020] Among them, the relative dosage of UEA expansion agent to sulphoaluminate cement is 4-10%, and the specific options are 4%, 5%, 6%, 7%, 8%, 9%, and 10%.

[0021] Among them, acrylic anhydride is in excess of PEG-200, and the molar ratio can be 1.1-1.3:1. Since the molecular weight of polyethylene glycol is the average molecular weight, for example, it is generally believed that the average molecular weight of PEG-200 is 190-210, PEG-400 is 380-420, and PEG-600 is 570-630. When converting here, the middle value of the above range is used as the measurement basis, for example, the molecular weight of PEG-200 is 200, PEG-400 is 400, and PEG-600 is 600. The reaction temperature is 60-80°C. The reaction time is 6-10h.

[0022] Among them, since butane sultone (i.e., 1,4-butane sultone) is extremely reactive and reacts strongly with amines, the reaction of N,N-dimethylacrylamide and butane sultone is carried out in a molar ratio of 1:1, and no excessive operation is required. This step needs to be carried out in a cold water bath or an ice water bath, and butane sultone is added slowly dropwise with strong stirring and the reaction is carried out in the open.

[0023] Among them, alkenyl carboxylic acid is a commercially available product, and products from regular manufacturers can be selected according to needs.

[0024] The amount of ammonium persulfate added is 0.1-0.8% of the total mass of the three monomers; the amount of mercaptopropionic acid added is 0.1-0.5% of the total mass of the three monomers.

[0025] The specific water reducer of the present invention and the cement-based grouting material for semi-flexible pavement containing the water reducer have at least the following beneficial effects: the specific structural design screened through a large number of experiments can achieve excellent water reduction and overcome the problem of slow setting of traditional polycarboxylic acid water reducers, achieve early strength, and make the slurry uniform and stable without the need for additional additives. DETAILED DESCRIPTION

[0026] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.

[0027] Example 1

[0028] (1) Add 500 mL of ethanol and 100 g of PEG-200 to a 1 L reactor, start stirring, and slowly drop a solution of 75 g of acrylic anhydride and 150 mL of ethanol at room temperature. After 0.5 h of dropwise addition, heat to 70 °C and react for 6 h. After the reaction is complete, remove the ethanol by rotary evaporation and vacuum dry to obtain 170 g of PEG-200 acrylic acid ester;

[0029] (2) Add 300 mL of ethanol and 50 g of N,N-dimethylacrylamide to a 1L wide-mouthed reactor, stir vigorously in an open, ice bath, and slowly drop a solution of 69 g of butane sultone and 200 mL of ethanol. The dropwise addition should be completed within 1 hour, and then react at room temperature for 3 hours. After the reaction is completed, remove the ethanol by rotary evaporation and vacuum dry to obtain 116 g of 4-(N,N-dimethyl-N-acryloyl)aminopropanesulfonic acid salt;

[0030] (3) Weigh 43 g of 3-butenoic acid, i.e., alkenyl carboxylic acid in which n is 1;

[0031] (4) Add the monomers from steps (1) to (3) and 1 L of deionized water into a 2 L reactor, stir, add 2 g of ammonium persulfate and 1.6 g of mercaptopropionic acid, stir to dissolve, and then maintain the temperature at 60 ° C for 10 h to obtain modified polycarboxylic acid water reducer A-1.

[0032] Example 1 is an exemplary synthesis process, and the feed amount can be adjusted proportionally according to actual needs to obtain a product of corresponding yield.

[0033] The performance test results based on the national standard GB / 8076-2008 for concrete admixtures showed a water reduction rate of 37%, compressive strength ratios of %: 3d=216, 7d=193, 28d=177; and the vertical expansion rate at 7d was 0.26%.

[0034] Comparative Example 1

[0035] The same test conditions used a commercially available high-performance polycarboxylate water-reducing agent with a water reduction rate of 26%, compressive strength ratio %: 3d=180, 7d=159; 28d=152; vertical expansion rate of 7d was 0.20%.

[0036] Example 2

[0037] Basically the same as Example 1, in step (3), the alkenyl carboxylic acid n is 2, 50g of 4-pentenoic acid, and a modified polycarboxylic acid water-reducing agent A-2 is obtained. The water reduction rate is 36%, and the compressive strength ratio is %: 3d=217, 7d=195, 28d=179; the vertical expansion rate at 7d is only 0.28%.

[0038] Example 3

[0039] Basically the same as Example 1, in step (3), the alkenyl carboxylic acid n is 3, 57g of 5-hexenoic acid, and a modified polycarboxylic acid water-reducing agent A-3 is obtained. The water reduction rate is 35%, and the compressive strength ratio is %: 3d=214, 7d=190, 28d=175; the vertical expansion rate at 7d is only 0.26%.

[0040] It can be seen from Examples 1-3 and Comparative Example 1 that the water reducer of the present invention has performance that meets national standards and has better effects in some aspects than commercially available high-efficiency water reducers.

[0041] Example 4

[0042] Cement-based grouting materials for semi-flexible pavement: 80 kg sulphoaluminate cement, 12 kg Grade II fly ash, 20 kg 200 mesh quartz sand, 15 kg 1.6 fineness coal power plant slag, 0.6 kg A-1 water reducer prepared in Example 1, 0.08 kg polydimethylsiloxane, and 5.4 kg UEA expansion agent.

[0043] Manually mix the above grouting materials with 40 kg of mixing water. After the mixture is evenly mixed, switch to electric stirring and stir at 480 rpm for 5 minutes. Then increase the speed to 800 rpm and continue stirring for 5 minutes to complete the mixing.

[0044] According to the test method of "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020), the initial fluidity of the grouting was tested to be 15.1s; the 7d flexural strength was 7.6Mpa, the 7d compressive strength was 34.3MPa; and the 7d vertical expansion rate was 0.25%.

[0045] Comparative Example 2

[0046] The A-1 water reducer prepared in Example 1 of Example 4 was replaced with the high-performance polycarboxylate water reducer of Comparative Example 1. The initial fluidity of the grouting was tested to be 14.6s; the 7d flexural strength was 5.2MPa, the 7d compressive strength was 27.3MPa; and the 7d vertical expansion rate was 0.17%.

[0047] Example 5

[0048] The A-1 water reducer prepared in Example 1 of Example 4 was replaced by the A-2 water reducer prepared in Example 2. The initial fluidity of the grouting was tested to be 15.0s; the 7d flexural strength was 7.9MPa, the 7d compressive strength was 35.0MPa; and the 7d vertical expansion rate was 0.22%.

[0049] Example 6

[0050] The A-1 water reducer prepared in Example 1 of Example 4 was replaced by the A-3 water reducer prepared in Example 3. The initial fluidity of the grouting was tested to be 15.3s; the 7d flexural strength was 7.1MPa, the 7d compressive strength was 34.1MPa; and the 7d vertical expansion rate was 0.26%.

[0051] It can be seen from Examples 4-6 and Comparative Example 2 that the grouting material of the present invention can meet the relevant national standards and has better performance than commercially available products in some aspects.

[0052] In this specification, the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the embodiments described later, the description is relatively simple, and the relevant parts can be referred to the partial description of the previous embodiments.

[0053] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A cement-based grouting material for semi-flexible pavement, characterized in that: Contains the following components in percentage by weight relative to sulphoaluminate cement: sulphoaluminate cement, 10-15% Grade II fly ash, 15-25% 40-200 mesh quartz sand, 15-25% 1.6-3 fineness coal power plant slag, 0.5-1% modified polycarboxylate water reducer, 0.01-0.2% defoamer, 4-10% UEA expansion agent; The preparation method of the modified polycarboxylate water-reducing agent is: (1) Polyethylene glycol acrylate is prepared by reacting acrylic anhydride with PEG-200; (2) N,N-dimethylacrylamide reacts with butane sultone to prepare 4-(N,N-dimethyl-N-acryloyl)aminobutane sulfonic acid salt, the structure of which is ; (3) Alkenyl carboxylic acids having the following structure: , where n = an integer from 1 to 3; (4) Deionized water is added to the reaction kettle, and then the monomers prepared in steps (1), (2) and (3) are added in a molar ratio of acrylate polyethylene glycol ester: 4-(N,N-dimethyl-N-acryloyl)aminobutanesulfonic acid inner salt: alkenyl carboxylic acid of 1:0.5-2:0.5-2, and an initiator ammonium persulfate and a chain transfer agent mercaptopropionic acid are added. The mixture is stirred at 40-60° C. for 6-10 hours, and then sodium hydroxide is added to adjust the pH to 6-7; The amount of ammonium persulfate added is 0.1-0.8% of the total mass of the three monomers; the amount of mercaptopropionic acid added is 0.1-0.5% of the total mass of the three monomers.

2. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: The fineness of slag from coal-fired power plants is 1.6-2.

3. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: In step (3), n is 1.

4. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: The reaction temperature of step (4) is 60°C.

5. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: In step (4), the molar ratio of polyethylene glycol acrylate: 4-(N,N-dimethyl-N-acryloyl)aminobutanesulfonic acid inner salt: alkenyl carboxylic acid is 1:1:

1.

6. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: The quartz sand is 200 mesh.

7. The cement-based grouting material for semi-flexible pavement according to claim 1, characterized in that: The fineness of slag from coal-fired power plants is 1.6.

Citation Information

Patent Citations

  • Cement-based grouting material for early strength type semi-flexible pavement

    CN107879702A

  • Cement-based grouting material for semi-flexible pavement

    CN118324463A